Analytical approaches to stabilization and adjustment programs - Mill, Cadman Atta (World Bank WashingtonUS, 1992)
Deals with issues related to the reform and transformation of open economies. Provides an analytical framework for policy formulation to help policymakers in developing countries to negotiate adjustment loans with the World Bank and the IMF. Presents the development community's criticisms of the Bank-Fund approaches to stabilization and structural adjustment.